2007
DOI: 10.1080/03639040600975238
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surfactant on the Thermal Behavior of Marigold Oil Emulsions with Liquid Crystal Phases

Abstract: Vegetable oils have been largely consumed owing to the interest of pharmaceutical and cosmetic industries in using natural raw materials. The production of stable emulsions with vegetable oils challenges formulators due to its variability in composition and fatty acids constitution within batches produced. In the present work, it was studied that the influence of the size of carbon chain and the number of ethylene oxide moieties of the surfactant on the thermal behavior of eight emulsions prepared with marigol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 17 publications
0
10
0
3
Order By: Relevance
“…Most food emulsions contain L a or L b phases, [12] and Professors Santos and Pedro have recently pointed out their importance for pharmaceutical emulsions. [13,14] The transformations found in the initial investigation of emulsion [11] evaporation could be deduced from the phase diagram, in spite of the obvious fact that the phase diagram reflects equilibrium conditions, while the evaporation is a kinetic process. The potential deviation from equilibrium conditions due to kinetic factors may be alleviated by focusing the phase diagram approach [15][16][17] on systems in which the main body of the vapor originates from the continuous phase or the evaporation from a bicontinuous structure, in which the diffusion rates of the compounds are of a similar magnitude as in the continuous phase.…”
Section: Introductionmentioning
confidence: 99%
“…Most food emulsions contain L a or L b phases, [12] and Professors Santos and Pedro have recently pointed out their importance for pharmaceutical emulsions. [13,14] The transformations found in the initial investigation of emulsion [11] evaporation could be deduced from the phase diagram, in spite of the obvious fact that the phase diagram reflects equilibrium conditions, while the evaporation is a kinetic process. The potential deviation from equilibrium conditions due to kinetic factors may be alleviated by focusing the phase diagram approach [15][16][17] on systems in which the main body of the vapor originates from the continuous phase or the evaporation from a bicontinuous structure, in which the diffusion rates of the compounds are of a similar magnitude as in the continuous phase.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the number of ethylene oxide moieties was not as significant as the carbon chain. 83 Following the trend of using natural compounds in systems containing nanostructured LCs, Santos et al proposed using vegetable oils from plants native to Brazil during evaluations for the formation of lamellar LC crystalline phases. The following vegetable oils were used: andiroba (Carapa guyanensis) Aubl (Meliaceae), apricot (Prunus armeniaca) (Rosaceae), avocado (Persea americana Mill) (Lauraceae), Brazil nut (Bertholletia excelsa Bonpl) (Lecythidaceae), Buriti (Mauritia flexuosa) (Arecaceae), cupuassu (Theobroma grandiflorum Willd.…”
Section: Liquid Crystalline Systemsmentioning
confidence: 99%
“…They also offer some protection against photo-or thermal degradation and can promote increased water retention in the stratum corneum, providing increased skin hydration. Finally, LCSs promote the sustained release of active substances and physicochemical stability of emulsions (Formariz et al, 2005;Santos, Rocha Filho, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…They also offer some protection against photo-or thermal degradation and can promote increased water retention in the stratum corneum, providing increased skin hydration. Finally, LCSs promote the sustained release of active substances and physicochemical stability of emulsions (Formariz et al, 2005;Santos, Rocha Filho, 2007).Liquid crystals are not generally employed in formulations of microbiological preservatives because they have large amounts of surfactants that suppress the growth of micro-organisms. Moreover, the high concentration of oil limits water access, which is one of the main causes of antimicrobial action (Oliveira et al, 2007).…”
mentioning
confidence: 99%